Mining the Protein Data Bank to inspire fragment library design - Revillo Imbernon, Julia; Chiesa, Luca; Kellenberger, Esther (Frontiers in Chemistry, 2023)
The fragment approach has emerged as a method of choice for drug design, as it allows difficult therapeutic targets to be addressed. Success lies in the choice of the screened chemical library and the biophysical screening method, and also in the quality of the selected fragment and structural information used to develop a drug-like ligand. It has recently been proposed that promiscuous compounds, i.e. those that bind to several proteins, present an advantage for the fragment approach because they are likely to give frequent hits in screening.